Penerapan Konsep Blue Economy Pada Budidaya Udang Vaname Melalui Pemetaan Stakeholder Di Kecamatan Rawajitu Timur Kabupaten Tulang Bawang - Ristiawati, Risa; Damai, Abdullah Aman; Rochana, Erna; Febryano, Indra Gumay; Riantini, Maya; Tresiana, Novita (Universitas Bangka Belitung, 2024)
The purpose of this study was to map the stakeholders involved in efforts to implement the concept of blue economy in vaname shrimp farming in East Rawajitu District, Tulang Bawang Regency. Data were collected using a qualitative approach through in-depth interviews and documentation studies. Data analysis was carried out descriptively to map the stakeholders involved based on their importance and influence. The results showed 21 stakeholders played a role consisting of private government, community and academics. Stakeholders who play a role as players are the Lampung Provincial Government, the Maritime and Fisheries Service, the Tulang Bawang Regency Government, the Tulang Bawang Regency Fisheries Service, which has a very strong interest and influence. Stakeholders who act as context setters are the Ministry of Marine Affairs and Fisheries, Ministry of Environment and Forestry, Commission IV of the House of Representatives, Lampung Marine Aquaculture Center, Mesuji Sekampung River Basin, Fish Quarantine Center for Quality Control and Safety of Fishery Products, INDOGAP Certification Institute, Seed Supplier, Shrimp Buyer, Feed and Medicine Company, P3UWL, KPBD, Yagasu, PPNI, LPMUKP, Universities have a large influence but low importance. The role of stakeholders in the subject category is shrimp farmers, who have a high interest but do not have a strong influence. Crowd stakeholders consist of the East Rawajitu District Government. Cross-sectoral cooperation must be carried out, so that the government's expectations towards applying the concept of blue economy or sustainable shrimp farming can be applied in protecting the environment while still increasing economic growth.